Psychological factors are associated with the outcome of physiotherapy for people with shoulder pain: a multicentre longitudinal cohort study. Issue 4 (21st July 2016) - Chester, Rachel; Jerosch-Herold, Christina; Lewis, Jeremy; Shepstone, Lee
Abstract : Background/aim: Shoulder pain is a major musculoskeletal problem. We aimed to identify which baseline patient and clinical characteristics are associated with a better outcome, 6 weeks and 6 months after starting a course of physiotherapy for shoulder pain. Methods: 1030 patients aged ≥18 years referred to physiotherapy for the management of musculoskeletal shoulder pain were recruited and provided baseline data. 840 (82%) provided outcome data at 6 weeks and 811 (79%) at 6 months. 71 putative prognostic factors were collected at baseline. Outcomes were the Shoulder Pain and Disability Index (SPADI) and Quick Disability of the Arm, Shoulder and Hand Questionnaire. Multivariable linear regression was used to analyse prognostic factors associated with outcome. Results: Parameter estimates (β) are presented for the untransformed SPADI at 6 months, a negative value indicating less pain and disability. 4 factors were associated with better outcomes for both measures and time points: lower baseline disability (β=−0.32, 95% CI −0.23 to −0.40), patient expectation of 'complete recovery' compared to 'slight improvement' as 'a result of physiotherapy' (β=−12.43, 95% CI −8.20 to −16.67), higher pain self-efficacy (β=−0.36, 95% CI −0.50 to −0.22) and lower pain severity at rest (β=−1.89, 95% CI −1.26 to −2.51). Conclusions: Psychological factors were consistently associated with patient-rated outcome, whereas clinical examination findings associated with a specific structural diagnosis were not. When assessing people with musculoskeletal shoulder pain and considering referral to physiotherapy services, psychosocial and medical information should be considered. Study registration: Protocol published at http://www.biomedcentral.com/1471-2474/14/192 .